Titanium boride / hydroxyapatite composite material and preparation and application thereof
Through the discharge plasma sintering process and the amount of TiB2 addition control, titanium boronide alloy/hydroxyapatite composites were prepared, which solved the shortcomings in strength and bioactivity of TC4 titanium alloy and HA composites, and achieved strengthening and improving bioactivity at low temperatures. It was suitable for oral implant materials.
Patent Information
- Application Number
- CN202510880705.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-02
AI Technical Summary
The existing TC4 titanium alloy and HA composite materials have shortcomings in taking into account both strength and biological activity. Especially in oral implant applications, the prior art is difficult to effectively sinter at low temperatures and maintain the mechanical properties and biological activity of the material.
The discharge plasma sintering process is used to combine the addition amount and temperature control of TiB2 to prepare titanium boronide alloy/hydroxyapatite composite material, and convert TiB2 into TiB, thereby achieving strengthening at low temperatures and improving biological activity.
The strength and biological activity of the material are significantly improved at lower temperatures, suitable for oral implant materials, with excellent mechanical properties and biocompatibility.
Smart Images

Figure CN120571075A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of composite materials, and in particular to the field of bio-implant composite materials. Background Art
[0002] Titanium and its alloys are widely used to replace human hard structures because of their high strength and the fact that they do not cause rejection reactions in the human body. Among them, TC4 is an α+β type titanium alloy with excellent fatigue resistance and machining properties. It can be processed into oral implant materials and serve in the human body for a long time. However, this material still has a certain probability of causing implant failure after being used for oral implants. There are two reasons for this: First, its elastic modulus is as high as 110GPa, which is much higher than that of alveolar bone (6-25GPa), which may lead to stress shielding and cause bone absorption. Second, it lacks biological activity and is difficult to form a stable chemical bond with bones.
[0003] Hydroxyapatite (Ca 10 (PO4)6OH (HA) is a component widely present in human bones and teeth, and synthetic HA also exhibits excellent biological properties. However, HA is difficult to process into complex shapes and has poor mechanical strength and toughness, making it difficult to withstand high loads and complex stress environments. Therefore, it is not suitable as a standalone oral implant material. To obtain implant materials with both excellent mechanical properties and bioactivity, researchers have recently focused on synthesizing composites of TC4 and HA. One strategy involves coating HA on the surface of TC4 using various coating methods, which can significantly improve its biological properties. However, limitations of this approach include the high elastic modulus of the resulting composites and the poor bonding strength between the coating and the substrate. Another strategy involves incorporating HA into a TC4 matrix using a powder sintering method to synthesize composites. Uniformly distributed HA can effectively reduce the elastic modulus of TC4 while imparting bioactivity. However, this method requires high preparation temperatures (above 1300°C) and long processing times (over 2 hours), which can lead to HA decomposition and gas generation. This not only compromises the biological properties of the composite but also interferes with the densification process. In addition, HA powder will adhere to the surface of TC4 powder, hindering the sintering of TC4 powder, resulting in structural defects such as cracks in the product, and having a negative impact on the strength of the composite material.
[0004] Therefore, developing low-temperature synthesis technology for TC4 and HA composites can inhibit HA decomposition and produce composites with excellent mechanical and biological properties. Borides react with Ti at relatively low temperatures to form an in-situ reinforcing phase, TiB, which strengthens low-temperature sintered TC4 and HA composites. Borides are biodegradable and easily metabolized and cleared by the body, reducing the risk of long-term accumulation and inflammation. Furthermore, boron can directly promote the proliferation and differentiation of osteoblasts while inhibiting bone resorption by suppressing osteoclast activity.
[0005] For example, Chinese patent document CN117265312A discloses a method for preparing a porous titanium boride alloy / fluorinated hydroxyapatite composite material, which is obtained by sintering a mixture containing TC4, TiB2, and FHA; the chemical expression of FHA is Ca 10 (PO4)6OH 2-2x F 2x , where x is 0.1-0.6; the weight ratio of TC4, TiB2, and FHA in the mixture is 86-94:3-7:3-7; and the sintering temperature is 1000°C-1100°C. This process, through the introduction of TiB2 and FHA, can improve sintering and bioperformance to a certain extent. However, to ensure good sintering behavior and performance, this solution requires a large amount of TiB2 and a high sintering temperature. While this can improve mechanical properties to a certain extent, the improvement needs to be improved. Furthermore, this solution exhibits limited bioactivity, and its ability to promote osseointegration needs to be enhanced. Summary of the Invention
[0006] In view of the problem that it is difficult to strike a balance between the strength and bioactivity of existing implant materials, the first purpose of the present invention is to provide a method for preparing a titanium boride alloy / hydroxyapatite composite material, aiming to prepare an implant material with both excellent strength and bioactivity.
[0007] The second purpose of the present invention is to provide a titanium boride alloy / hydroxyapatite composite material prepared by the preparation method and its application.
[0008] The third object of the present invention is to provide an implant material comprising the titanium boride alloy / hydroxyapatite composite material.
[0009] Research conducted by the present invention shows that the addition of TiB2 can improve the sintering properties of titanium alloys. However, the existing sintering process still requires a more demanding sintering process and a higher TiB2 content. Although this can achieve good implant material strength, it also brings new problems such as unsatisfactory bioactivity. Therefore, it is still difficult for the existing technology to make sintered implants have good strength and bioactivity. In response to the problems caused by TiB2, the present invention has conducted in-depth research and provides the following improvement solutions:
[0010] A method for preparing a titanium boride alloy / hydroxyapatite composite material, comprising spark plasma sintering a mixture comprising TC4, TiB2, and HA;
[0011] In the mixture, the content of TiB2 is 0.5-2.5 wt.%; the content of HA is 3-6 wt.%;
[0012] The sintering temperature is 700℃~830℃.
[0013] The present invention innovatively adopts the spark plasma sintering process to sinter a mixture containing TiB2, and further cooperates with the joint control of the TiB2 addition content and temperature. This can unexpectedly achieve the strengthening of titanium alloy at a lower temperature based on the mechanism of efficient sintering of TiB2 into TiB, thereby significantly improving its strength. Not only that, it can also effectively improve the biological activity of the sintered material, thereby achieving a balance of multiple advantages such as strength and biological activity.
[0014] In the present invention, HA is hydroxyapatite, which can be obtained by existing methods, for example, can be prepared by a co-precipitation method, the steps of which are: obtaining a solution A containing a calcium source; and a solution B containing a phosphorus source; adding solution B dropwise to solution A to perform co-precipitation to obtain the hydroxyapatite; the molar ratio of Ca in solution A to P in solution B is 1.50 to 2.00, preferably 1.67 to 1.70.
[0015] The calcium source may be at least one of calcium nitrate and calcium chloride;
[0016] The phosphorus source may be at least one of ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate;
[0017] Preferably, the temperature in the coprecipitation reaction stage is 20-70°C, more preferably 60-65°C;
[0018] Preferably, during the coprecipitation reaction, ammonia water is used to adjust the pH to 9.5 to 11, more preferably 9.9 to 10.1.
[0019] The average particle size of the HA prepared in the above coprecipitation step is ∼300 nm (eg, 100-250 nm), and the thermal decomposition temperature is ≥1000°C.
[0020] In the present invention, TC4 may be a commercial product or may be obtained by an existing method, and its D50 may be 10 to 50 μm.
[0021] In the present invention, the TiB2 can be a commercial product, and its average particle size can be 100 to 300 nm.
[0022] In the present invention, the components are mixed by acoustic resonance and ball milling to form a mixture that meets sintering requirements.
[0023] In the present invention, the spark plasma sintering process is innovatively adopted to sinter the powder material containing TiB2. The joint control of the TiB2 content and the sintering temperature is further coordinated to induce the mild conversion of TiB2 into TiB, thereby achieving the key to achieving the strength and bioactivity of the sintered titanium alloy.
[0024] Preferably, the TiB2 content in the mixture is 1-1.5 wt.%, and the HA content is 4.5-5.5 wt.%. In the present invention, the total content of each component is 100 wt.%. In the present invention, while significantly reducing the TiB2 content in the mixture, combined control of parameters such as sintering method and temperature can further achieve synergy, help further facilitate the gentle conversion of TiB2 to TiB, and improve the strength and bioactivity of the sintered titanium alloy.
[0025] In the present invention, the temperature of the spark plasma sintering process is 730-800° C., and can further be 740-760° C. The preferred temperature of the present invention is helpful to further synergistically improve the comprehensive properties of the material, such as strength and bioactivity.
[0026] In the present invention, spark plasma sintering technology is used to achieve sintering of the material;
[0027] The uniaxial pressure applied during sintering is 20 to 40 MPa.
[0028] The sintering time is 3 to 15 minutes, preferably 4 to 10 minutes.
[0029] The sintering process is carried out in vacuum.
[0030] The present invention also provides a titanium boride alloy / hydroxyapatite composite material prepared by the preparation method.
[0031] The present invention also provides an application of the titanium boride alloy / hydroxyapatite composite material prepared by the preparation method, which is used to prepare a biological implant material.
[0032] In a preferred application, the implant material is an implant material, preferably an oral implant material.
[0033] The present invention also provides a bioimplant material, comprising the titanium boride alloy / hydroxyapatite composite material prepared by the preparation method of the present invention, or prepared by the titanium boride alloy / hydroxyapatite composite material.
[0034] Beneficial effects
[0035] The present invention innovatively adopts the spark plasma sintering process to sinter a mixture containing TiB2, and further cooperates with the joint control of the TiB2 addition content and temperature. This can unexpectedly achieve the strengthening of titanium alloy at a lower temperature based on the mechanism of efficient sintering of TiB2 into TiB, thereby significantly improving its strength. Not only that, it can also effectively improve the biological activity of the sintered material, thereby achieving a balance of multiple advantages such as strength and biological activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The current and real-time temperature change curve of SPS at 600-800°C in the embodiment
[0037] Figure 2 The XRD diffraction patterns of the composite materials prepared in Examples 1 and 2, and the ratio of the strongest diffraction peak area of HA / Ti6Al4V (i.e., the relative content of HA)
[0038] Figure 3 SEM-EDS analysis of the composite material prepared in Examples 1 and 2
[0039] Figure 4 The density, porosity, compressive strength, compression modulus and Vickers microhardness of the composite materials in Examples 1 and 2 are shown in FIG.
[0040] Figure 5 The water contact angle diagram of the composite material in Examples 1 and 2, and the ion release in simulated body fluid (SBF)
[0041] Figure 6 SEM images of surface deposits of the composite materials in Examples 1 and 2 after immersion in SBF for 14 days (commercial TC4 titanium alloy was used as a control)
[0042] Figure 7 The following are SEM images of cells cultured on the composite materials of Examples 1 and 2 for one day, cell proliferation activity measured by CCK-8 assay after 1, 3, and 5 days of culture, and ALP activity of these samples measured by p-nitrophenol concentration after 7 days of osteoinduction (commercial TC4 titanium alloy was used as a control). DETAILED DESCRIPTION
[0043] The present invention will be further described in detail below with reference to specific embodiments. Obviously, the embodiments described are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0044] The present invention provides a titanium boride alloy / hydroxyapatite composite material (also known as TC4 / TiB / HA) containing a crystalline HA phase, having high strength and excellent bioactivity. The preparation process is as follows: TC4 powder, TiB2 powder, and HA are pre-mixed by acoustic resonance and high-energy ball milling to obtain a mixture, which is pre-pressed into a graphite mold and then spark plasma sintered in a vacuum to obtain the titanium boride alloy / hydroxyapatite composite material.
[0045] In the present invention, the HA (Ca 10 (PO4)6OH2) is prepared by a coprecipitation method using Solution A (calcium nitrate solution) and Solution B (diammonium hydrogen phosphate solution). Solution B is added dropwise to Solution A. During the reaction, the solution is heated in a water bath to a temperature of 20-70°C. The pH is adjusted to 9.5-11 with aqueous ammonia. The Ca / P molar ratio of the suspension after the reaction is 1.50-2.00. The suspension is aged at room temperature for 6-24 hours, then washed, filtered, dried, ground, and calcined at 800°C for 90 minutes.
[0046] In a preferred embodiment, the reaction temperature is 60-65° C., the pH is 9.9-10.1, the Ca / P molar ratio in the suspension after the reaction is 1.67-1.70, and the aging time is 24 h.
[0047] The prepared HA needs to undergo laser particle size analysis and thermal decomposition testing to ensure that the average particle size is ≤500nm and the thermal decomposition temperature is ≥1000℃.
[0048] As an optional solution, among TC4, TiB2, and HA, TiB2: 0.5-2 wt.%, HA: 5±0.5 wt.%, and the balance is TC4. More preferably, TC4: 94 wt.%, TiB2: 1 wt.%, and HA: 5 wt.%.
[0049] As an optional solution, the average particle size of the TC4 powder is 10 to 50 μm, the average particle size of the TiB2 powder is 250±20 nm, and the average particle size of the HA powder is 300 nm.
[0050] The mixing acceleration is 10 to 100 g (g refers to the acceleration due to gravity), and the mixing time can be 300 to 600 s.
[0051] The parameters of the ball milling are: ball-to-material ratio of 5 to 15:1, ball milling time of 10 to 30 hours, and rotation speed of 150 to 250 r / min.
[0052] The uniaxial pressure applied during the SPS sintering is 20-40 MPa. Furthermore, the uniaxial pressure applied during the sintering is 40 MPa.
[0053] The SPS sintering should be performed in vacuum.
[0054] Preferably, the SPS sintering temperature is 700°C to 830°C.
[0055] In a preferred embodiment, the SPS sintering time is 5 to 10 minutes.
[0056] Further preferably, the microwave sintering time is 5 minutes.
[0057] The present invention provides an application of a titanium boride alloy / hydroxyapatite composite material, and uses the titanium boride alloy / hydroxyapatite composite material as an oral implant material.
[0058] Evaluation of biological properties of materials:
[0059] The composite material was immersed in simulated body fluid (SBF). The pH of the SBF solution was measured on days 0, 2, 4, 6, 8, 10, 12, and 14 of the experiment, and the concentrations of Ca and P ions in the solution were determined using ICP. After immersion, the samples were removed, cleaned, dried, and gold-sprayed. The surface morphology and elemental composition of the samples after immersion were examined using SEM-EDS. Cell proliferation on the surface of the material was evaluated using the CCK-8 assay. The effects of the composite material on cell osteogenesis and mineralization were also examined using an alkaline phosphatase (ALP) activity assay.
[0060] The following is a specific implementation plan:
[0061] Example 1:
[0062] Step (1): Preparation of HA:
[0063] Prepare Solution A (calcium nitrate solution) and Solution B (diammonium hydrogen phosphate solution). Add Solution B dropwise to Solution A. Heat the solution in a water bath to 60-65°C during the reaction. Adjust the pH to 9.9-10.1 with aqueous ammonia. The Ca / P molar ratio in the suspension after the reaction is 1.67-1.70. After aging at room temperature for 24 hours, wash, filter, dry, grind, and calcine at 800°C for 90 minutes. The average particle size is 240 nm. Testing shows no thermal decomposition at 1000°C.
[0064] Step (2):
[0065] A certain amount of TC4 (average particle size 17 μm), TiB2 (average particle size 250 nm), and the aforementioned HA powder were premixed by acoustic resonance at a mass ratio of 94 wt.% TC4 + 1 wt.% TiB2 + 5 wt.% HA to obtain a mixed raw material. The mixing process was performed at a stirring acceleration of 50 g and a mixing time of 300 s. The premixed powder was placed in a vacuum ball mill, and grinding balls were added in sequence at a ball-to-material ratio of 10:1. The mill was evacuated in a sealed state, filled with argon, and milled in a planetary ball mill for 12 hours at 200 rpm. After ball milling, the mill was placed in a vacuum glove box and the powder was removed.
[0066] Step (3):
[0067] The above powders were loaded into a Φ20mm graphite mold, placed in an SPS sintering system, and sintered under vacuum. The heating rate was set to 100℃ / min, and a constant uniaxial pressure of 40MPa was applied during the sintering process. After the system temperature reached 750℃ (sintering temperature), it was kept warm for 5 minutes, then unloaded and cooled with the furnace. The mechanical properties of the sintered samples were evaluated (including compressive strength, hardness, bulk density, elastic modulus, porosity, contact angle, etc.). The ability of the material to induce apatite mineralization was tested using simulated body fluid (SBF). Human osteosarcoma cell line (MG-63) was cultured on the sample surface to detect the sample's biocompatibility (cell adhesion and proliferation activity) and bioactivity (alkaline phosphatase activity).
[0068] Control group: commercial TC4 titanium alloy
[0069] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 544.2 MPa, the hardness is 297.0 HV, and the volume density is 3.66 g / cm 3, compression modulus of 12.28GPa, porosity of 13.55%, and contact angle of 36.8°. During the 14-day immersion process of the sample, the degradation and absorption of Ca and P ions, as well as the change in pH, can be detected. After 7 days of immersion, it can be observed that apatite has completely covered the surface of the sample, forming a coating of uniform thickness. After 14 days of immersion, it can be observed that the coating has significantly thickened, proving that the composite material has excellent biological activity. In the CCK-8 analysis method, absorbance is used to quantitatively represent cell proliferation activity. The absorbance of the sample after 1, 3, and 5 days of cell culture was 0.36, 0.80, and 1.06, respectively, which is significantly better than the TC4 titanium alloy in the control group (the absorbance after 1, 3, and 5 days of culture was 0.20, 0.23, and 0.24, respectively), indicating that the sample has excellent cell proliferation activity. In the ALP activity analysis method, the p-nitrophenol content is used to quantitatively represent the cell osteogenic activity. The p-nitrophenol content of this sample was 76.34 μM after cell inoculation and osteogenic induction for 7 days, which was significantly better than the TC4 titanium alloy in the control group (28.83 μM), indicating that this sample has the functionality of promoting osteoblast differentiation.
[0070] Example 2
[0071] Compared with Example 1, the only difference is that the sintering temperature of SPS sintering in step (3) is changed to:
[0072] Group A: 600℃
[0073] Group B: 650℃
[0074] Group C: 700℃
[0075] Group D: 800℃
[0076] Group E: 550℃
[0077] Group F: 850℃
[0078] Other operations and parameters are the same as in Example 1.
[0079] Tested according to the method of Example 1, the results were:
[0080] Group A:
[0081] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 58.8 MPa, the hardness is 104.7 HV, and the volume density is 3.05 g / cm 3 The sample has a compression modulus of 1.87 GPa, a porosity of 28.18%, and a contact angle of 24.9°. During the 14-day immersion process, degradation and absorption of Ca and P ions, as well as changes in pH, were detected. An apatite layer covering the sample surface was observed after 14 days of immersion.
[0082] Group B:
[0083] The prepared titanium boride alloy / hydroxyapatite composite implant material has a compressive strength of 77.8 MPa, a hardness of 109.0 HV, and a bulk density of 3.10 g / cm 3 The sample has a compression modulus of 2.04 GPa, a porosity of 27.04%, and a contact angle of 25.2°. During the 14-day immersion process, degradation and absorption of Ca and P ions, as well as changes in pH, were detected. An apatite layer covering the sample surface was observed after 14 days of immersion.
[0084] Group C:
[0085] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 171.7 MPa, the hardness is 239.7 HV, and the volume density is 3.25 g / cm 3 , compression modulus of 5.67 GPa, porosity of 24.21%, and contact angle of 33.0°. During the 14-day immersion process, the degradation and absorption of Ca and P ions, as well as changes in pH, were detected. An apatite layer covering the surface of the sample was observed after 14 days of immersion. The absorbance of the CCK-8 assay after 1, 3, and 5 days of cell culture was 0.19, 0.40, and 0.55, respectively. The ALP activity assay measured a p-nitrophenol content of 57.21 μM after 7 days of osteogenic induction.
[0086] Group D:
[0087] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 953.5 MPa, the hardness is 344.7 HV, and the volume density is 4.04 g / cm 3 , compression modulus of 19.26 GPa, porosity of 6.06%, and contact angle of 45.8°. During the 14-day immersion process, the degradation and absorption of Ca and P ions, as well as changes in pH, were detected. An apatite layer covering the surface of the sample was observed after 14 days of immersion. The absorbance of the CCK-8 assay after 1, 3, and 5 days of cell culture was 0.19, 0.29, and 0.29, respectively. The ALP activity assay measured a p-nitrophenol content of 49.62 μM after 7 days of osteogenic induction.
[0088] Group E:
[0089] The composite powder failed to sinter to form a dense titanium boride alloy / hydroxyapatite composite implant material, with a compressive strength of less than 50 MPa and a hardness too low to obtain accurate data.
[0090] Group F:
[0091] The obtained composite material has a compressive strength of 1120.8 MPa, a hardness of 406.3 HV, and a bulk density of 4.18 g / cm 3 , elastic modulus of 10.25 GPa, porosity of 2.79%, and contact angle of 82.3°. No HA crystalline phase was detected in the sample. During the 14-day immersion process, the Ca and P ion concentrations and pH did not change significantly. No noticeable sediment layer formed after 14 days of immersion, indicating that the bioactivity of the composite material is relatively limited.
[0092] It can be seen from Examples 1 and 2 that, for the material containing TiB2 described in the present invention, controlling the temperature of the spark plasma sintering process to be within the range of 700-830°C required by the present invention can unexpectedly obtain good sintering strength and bioactivity.
[0093] Example 3
[0094] Compared with Example 1, the only difference is that the ingredients and proportions of the mixed raw materials in step (2) are changed. The total amount of raw materials is the same. The experimental groups are:
[0095] Group A: The mixed raw material composition is: 94.5% TC4 + 0.5% TiB2 + 5% HA;
[0096] Group B: The mixed raw material composition is: 93% TC4+2% TiB2+5% HA;
[0097] Comparative group A: The mixed raw material composition is: 90% TC4+5% TiB2+5% HA;
[0098] Comparative group B: the mixed raw material contained 95% TC4 + 5% HA and lacked TiB2;
[0099] Other operations and parameters are the same as in Example 1;
[0100] Tested according to the method of Example 1, the results were:
[0101] Group A:
[0102] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 392.6 MPa, the hardness is 268.7 HV, and the volume density is 3.56 g / cm 3 , compression modulus of 9.69 GPa, porosity of 16.23%, and contact angle of 26.6°. During the 14-day immersion process, degradation and absorption of Ca and P ions, as well as changes in pH, were detected. Apatite completely covered the sample surface after 7 days of immersion, forming a uniform coating. Further thickening of the coating was observed after 14 days of immersion.
[0103] Group B:
[0104] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 424.3 MPa, the hardness is 335.3 HV, and the volume density is 3.52 g / cm 3 , compression modulus of 10.53 GPa, porosity of 17.67%, and contact angle of 25.7°. During the 14-day immersion process, degradation and absorption of Ca and P ions, as well as changes in pH, were detected. Apatite completely covered the sample surface after 7 days of immersion, forming a uniform coating. Further thickening of the coating was observed after 14 days of immersion.
[0105] Comparison group A:
[0106] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 342.5 MPa, the hardness is 353.0 HV, and the volume density is 3.41 g / cm 3 , compression modulus of 8.86 GPa, porosity of 19.28%, and contact angle of 27.7°. During the 14-day immersion process of the sample, the degradation and absorption of Ca and P ions, as well as the change in pH, can be detected. After 7 days of immersion, it can be observed that apatite has completely covered the surface of the sample, forming a coating of uniform thickness. After 14 days of immersion, the coating can be observed to be further thickened. However, the TiB2 in this sample was not completely converted into the reinforcing phase TiB in situ, and the number of wrinkled cells in the cell adhesion test was large, indicating that the composite material has certain cytotoxicity.
[0107] Comparison group B:
[0108] The compressive strength of the titanium alloy / hydroxyapatite composite implant material is 286.6 MPa, the hardness is 193.3 HV, and the volume density is 3.23 g / cm 3 , compression modulus of 7.35 GPa, porosity of 23.65%, and contact angle of 34.4°. During the 14-day immersion process of the sample, the degradation and absorption of Ca and P ions, as well as the change in pH, were detected. It was observed that the apatite layer failed to completely cover the sample surface after 14 days of immersion. Compared with the above-mentioned Example 1, the sintered density of the composite material was significantly reduced, and the degree of decomposition of HA increased, resulting in poor biological properties of the material.
[0109] Example 4
[0110] Compared with Example 1, the only difference is that the sintering time of step (3) is changed to 10 min.
[0111] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 553.6 MPa, the hardness is 293.7 HV, and the volume density is 3.68 g / cm3 , compression modulus is 12.44GPa, porosity is 13.44%, and contact angle is 37.1°. During the 14-day immersion process of the sample, the degradation and absorption of Ca and P ions, as well as the change of pH can be detected. It can be observed that the apatite has completely covered the surface of the sample after 7 days of immersion, forming a coating with uniform thickness. After 14 days of immersion, it can be observed that the coating has been significantly thickened, which proves that the composite material has excellent biological activity. In the CCK-8 analysis method, absorbance is used to quantitatively represent cell proliferation activity. The absorbance of the sample after 5 days of cell culture is 1.03. The content of p-nitrophenol after 7 days of osteogenic induction in the ALP activity analysis method is 75.68μM. In summary, the overall effect of this embodiment is close to that of Example 1. From the perspective of energy conservation, Example 1 is a better solution.
[0112] Comparative Example 1
[0113] Compared with Example 1, the difference is that microwave sintering technology is used to achieve powder sintering. Specifically, in order to make the powder form agglomerates before sintering, in step (2), 3wt.% stearic acid is additionally added as a binder during ball milling, and a precision servo hydraulic press is used to press the powder into cylindrical agglomerates under the conditions of a pressure of 900MPa and a holding time of 45s. Then, the difference in step (3) is that the pressed cylindrical agglomerates are first placed in a tube furnace at 380°C under a high-purity argon atmosphere to remove the binder, and then the powder is prepared using a microwave sintering process, with the sintering time extended to 30 minutes and the sintering atmosphere being high-purity argon.
[0114] The resulting titanium boride alloy / hydroxyapatite composite implant material exhibited a low degree of sintering and a compressive strength of only 44.2 MPa. The compression curve exhibited a jagged shape, making it impossible to fit the compression modulus. Furthermore, the hardness was very low, with no reading on the durometer. In summary, this embodiment clearly failed to meet the application requirements of implants.
[0115] Comparative Example 2
[0116] Compared with Comparative Example 1, the only difference is that in step (3), the temperature of microwave sintering is controlled to 1050°C.
[0117] The compressive strength of the titanium boride alloy / hydroxyapatite composite implant material is 740.4 MPa, the hardness is 366.0 HV, and the volume density is 4.04 g / cm 3, a compression modulus of 12.21 GPa, a porosity of 9.09%, and a contact angle of 44.1°. During the 14-day immersion process, degradation and absorption of Ca and P ions, as well as changes in pH, were detected in this sample. In the ALP activity assay, p-nitrophenol content is used to quantitatively indicate cell osteogenic activity. Seven days after cell inoculation and osteogenic induction, the p-nitrophenol content in this sample was 53.28 μM, superior to the TC4 titanium alloy control group (28.83 μM), but inferior to Example 1 (76.34 μM).
[0118] In summary, the comprehensive osteogenic induction ability of the titanium boride alloy / hydroxyapatite composite implant material prepared by SPS technology in Example 1 at the cellular level is significantly better than that of the titanium boride alloy / hydroxyapatite composite implant material prepared by microwave sintering technology in the comparative example, and the preparation process in Example 1 is shorter and the sintering temperature is lower, which has the advantages of energy saving and efficiency improvement.
Claims
1. A method for preparing a titanium boride alloy / hydroxyapatite composite material, characterized in that: The mixture containing TC4, TiB2 and HA is subjected to spark plasma sintering; In the mixture, the content of TiB2 is 0.5-2.5 wt.%; the content of HA is 3-6 wt.%; The temperature of the spark plasma sintering process is 700°C to 830°C.
2. The preparation method according to claim 1, wherein: Nano HA was prepared by co-precipitation method, the steps of which are: Obtaining a solution A containing a calcium source; and a solution B containing a phosphorus source; adding solution B dropwise to solution A to perform a coprecipitation reaction to obtain the hydroxyapatite; The molar ratio of Ca in solution A to P in solution B is 1.50 to 2.
00.
3. The preparation method according to claim 1, wherein: In the mixture, the content of TiB2 is 1-1.5wt.%; the content of HA is 4.5-5.5wt.%.
4. The preparation method according to claim 1, wherein: The temperature of the spark plasma sintering process is 730-800°C, and can further be 740-760°C.
5. The preparation method according to claim 1, wherein: The uniaxial pressure applied during the spark plasma sintering process is 20 to 40 MPa.
6. The preparation method according to claim 1, wherein: The sintering time of the spark plasma sintering process is 3 to 15 minutes, preferably 4 to 10 minutes.
7. A titanium boride alloy / hydroxyapatite composite material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of a titanium boride alloy / hydroxyapatite composite material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The bioimplant material is prepared using the same.
9. Use of the titanium boride alloy / hydroxyapatite composite material obtained by the preparation method according to claim 8, characterized in that: The implant material is an implant material, preferably an oral implant material.
10. A biological implant material, characterized in that: The titanium boride alloy / hydroxyapatite composite material comprises the titanium boride alloy / hydroxyapatite composite material prepared by the preparation method according to any one of claims 1 to 6, or is prepared by the titanium boride alloy / hydroxyapatite composite material.
Citation Information
Patent Citations
Porous titanium boride alloy / fluorinated hydroxyapatite composite material as well as preparation and application thereof
CN117265312A